PEMANFAATAN OBJEK WISATA PULAU KUCING DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT DI DESA FUKWEU KECAMATAN SANANA KABUPATEN KEPULAUAN SULA - Taroreh, Wirna; Paat, Cornelius; Tumiwa, Juliana (HOLISTIK, Journal Of Social and Culture, 2019)
Indonesia is a country that has a natural beauty that comes with its own characteristics and cultural diversity, necessitating an increase in the tourism sector in order to utilize the natural resources, especially in Indonesia. Monsen in Pitana (2005). This is because tourism is a sector which is considered profitable and potential to be developed as one of the assets that are used as a source of income for the people and the State. Tourism is one that can not be separated to become the flagship program in every region in Indonesia as Bali became a tourist destination (DTW) most popular in Indonesia. Not just in Bali who got the recognition of international level. Up in the easternmost region in Papua Indonesia namely the fame with the beauty of the sights of Raja Ampat. In the utilization of interest often raises various problems that can often occur in the community therefore desperately needed close attention from local governments in order to give an understanding in the community so that the community does not misapply about utilization of tourist attractions. The island cats are utilized for the benefit of society and nature sustainability while keeping in the village of Fukweu has given a positive impact against the economic activities that can lift the welfare of society in particular local communities, in utilization of Cat Island tourist attraction no doubt will lead to the man who is the perpetrator.. Keywords: tourism, resources, impact